Retinal Ganglion Cell Death of Guinea Pig is Slower Than Rat as Optic Nerve Transection Animal Model - Tomohiko Sasase; Fatchiyah Fatchiyah; Takeshi Ohta (JSMARTech, 2023)
Glaucoma is a progressive optic neuropathy that leads to retinal ganglion cell (RGC) apoptosis and is a leading cause of acquired blindness. Recently, lack of clinical protective treatment for optic nerve in glaucoma thus inhibitor drugs towards progression of RGC degeneration are urgently needed. In this study, we established a guinea pig optic nerve transection model and investigated the conditions under which RGC death is evaluated in the development of retinal neuroprotective drugs for the treatment of glaucoma. Guinea pig optic nerve axotomy induces RGC death similarly to other rodent models; however, the time to progress to significant RGC death is 21 days after transection and is longer than in the rat, 10 days after optic nerve axotomy. The results are useful for evaluating species-specific optic neuroprotective agents against rats and mice.